Teamwork Training in Organizations: The Case of Training Resource Management - Salas, Eduardo; Kosarzycki, Mary P.; Wilson, Katherine A.; DeRouin,Renée (Psykhe, 2002)
As organizations increasingly rely on teams 10 accomplish operational and strategic goals, attention has centered on both the identification and training of requisite team skills. The structured approach to team training known as Crew Resource Management (CRM) training offers a highly effective paradigm that can be adapted to the specific needs of many organizations. The major highlights of this paper are: (a) a discussion of the requirements for training teams to work together effectively, (b) a presentation of five case studies that demonstrate how CRM training designed for aviation environments can be adapted to meet the unique conditions of other organizations, and (c) recommended guidelines for CRM implementation in non-aviation settings. Finally, the authors recommend extending CRM which is applicable to higlvimpact work organizations, to include the types of teams more frequently found in organizations.